The effect of training in different playing areas on developing some physical and skill abilities in intermediate male football players aged 17-19 years - sahraoui, Mourad; Bourenane Cherif, Mostefa; smail, sadek (sports creativity, 2025)
The training process requires knowledge and field practice, and relying on field experience without resorting to scientific knowledge undermines one of the basic rules for developing, refining, and growing that experience. As a result of the researchers' observation and follow-up of the latest developments in this game and their experience in the fields, whether as players or coaches, it became clear that there are different opinions about training in different spaces, methods of training them, and how to utilize them. The researchers found that there is ambiguity and a lack of clarity in the vision of most coaches in accessing the vocabulary of these trainings and the latest methods for them and how to utilize them in developing specific physical and skill abilities by finding scientific formulas to adopt during the training process using the latest methods. This was the reason that prompted the researchers to delve into this field and find a formula by designing a special program for training in different spaces by controlling the various elements of the training process without neglecting the aspects that need to be developed. Playing drills in various small and large spaces aim to develop different skills, including ball possession and building attacks in different areas of the field. These drills are a primary method used in player training. Muwaffaq Al-Mawli explains that these drills, played in small and large spaces within squares or rectangles, and performed from different positions on the field, cultivate and develop individual skills such as dribbling, feinting, and other maneuvers. They also enhance the player's technical skills for the benefit of the team collectively through the optimal and varied selection of ground, high, diagonal, and short passes, as well as through one-touch play and ball retention. The more comprehensive this type of training is, the closer it comes to competition in terms of excitement, competitiveness, and even physical and technical aspects. This places the player in a situation similar to what they face during competition through the harmony between the interplay between the art of movement and the players' physical capabilities. Researchers have analyzed player performance during various matches to identify key tactical phrases and formulate them into drills that closely resemble what occurs in matches.